2021
DOI: 10.48550/arxiv.2108.01282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the FRB host galaxy population and its connection to transients in the local and extragalactic Universe

Shivani Bhandari,
Kasper E. Heintz,
Kshitij Aggarwal
et al.

Abstract: We present the localization and host galaxies of one repeating and two apparently non-repeating Fast Radio Bursts. FRB 20180301A was detected and localized with the Karl G. Jansky Very Large Array to a star-forming galaxy at z = 0.3304. FRB20191228A, and FRB20200906A were detected and localized by the Australian Square Kilometre Array Pathfinder to host galaxies at z = 0.2430 and z = 0.3688, respectively. We combine these with 13 other well-localised FRBs in the literature, and analyse the host galaxy properti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Indeed, the ratio for SDSS J0158+6542 lies above the envelope of the ratios for the xGASS galaxies with comparable sSFR values, indicating that SDSS J0158+6542 is a gas-rich galaxy. Further, SDSS J0158+6542 lies well below the star-forming main sequence, and is almost a quiescent galaxy (Bhandari et al 2021). The combination of gas-richness and near-quiescence indicates that SDSS J0158+6542 has acquired significant amounts of HI in the recent past.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, the ratio for SDSS J0158+6542 lies above the envelope of the ratios for the xGASS galaxies with comparable sSFR values, indicating that SDSS J0158+6542 is a gas-rich galaxy. Further, SDSS J0158+6542 lies well below the star-forming main sequence, and is almost a quiescent galaxy (Bhandari et al 2021). The combination of gas-richness and near-quiescence indicates that SDSS J0158+6542 has acquired significant amounts of HI in the recent past.…”
Section: Resultsmentioning
confidence: 96%
“…We used PATH in our simulations in order to incorporate the most robust means in the literature to perform this association, and to be able to easily simulate the effects of modifying our assumptions. We simulated somewhat large FRB localisation regions (FHWM of 1 arcsec), and shallow optical observations (the PanSTARRS limit of 𝑚 𝑟 = 23.2) in order to better highlight the effects of the optical selection bias; some FRBs used in current studies (e.g., Bhandari et al 2021) are better localised, and most have deeper optical observations than are available from PanSTARRS. Current samples are therefore not likely to be subject to optical selection biases as large as those we identify.…”
Section: Tuning Pathmentioning
confidence: 99%
“…A Hubble Space Telescope study of the environments of a sample of eight FRBs with sub-arcsecond localisations revealed a link with spiral-arm structures, but generally unremarkable underlying stellar-mass and SFR densities (Mannings et al 2020). Comparisons of the host-galaxy properties and projected physical offsets 2 of FRBs with populations of other extragalactic transients and compact objects generally indicate similarities with LGRBs and CCSNe, but little else (Bochenek et al 2021;Bhandari et al 2021). The wide diversity in host galaxies and host environments within the FRB population paints an inconsistent picture, possibly hinting at multiple progenitor channels, or possibly implicating selection biases in the observed FRB sample.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations